Bridging the Divisum: A Rare Case of Pancreaticopleural Fistula in the Setting of Complete Pancreatic Divisum Treated Endoscopically - Rachel Peterson; Samiran Mukherjee MBBS; Prateek Suresh Harne MBBS; Sahir Quraeshi MD; Anuj Vikrant Sharma MD; Umair Masood MD; Divey Manocha MD (SAGE Publishing, 2020)
A pancreaticopleural fistula (PPF) is a rare complication of chronic pancreatitis that occurs either due to a pancreatic duct disruption or a pseudocyst extension. A pancreatic divisum, on the other hand, is a common anatomic variant of the pancreas that is rarely symptomatic. We describe a case of recurrent pleural effusion in a patient with a history of chronic pancreatitis. Investigations revealed the presence of a PPF and a concomitant complete pancreatic divisum. There was resolution of the pleural effusion on endoscopic therapy. This is the fourth reported case of a PPF in the setting of complete pancreatic divisum and the first reported case in a middle-aged female.